NEEDS ANALYSIS OF ENGLISH FOR STUDENTS OF SPA TRAINING PROGRAM - Muliana, I Wayan; Suprastayasa, I Gusti Ngurah Agung; Darmawijaya, I Gede (JURNAL KEPARIWISATAAN, 2010)
In response to the booming of the spa industry. STP Nusa Dua Bali has launched a Spa Training Program, aiming at preparing students to be able to work professionally in international spa outlets/industries. Besides spa vocational subjects English is a crucial subject in the Program in order to enable the students to communicate effectively and appropriately with foreign guests and customers in handling their future job. Since Spa was a new program at STP Nusa Dua Bali, this research was conducted/or identifying the profile of the learners 'target needs of English language course in the Spa Training Program, specifically. at basic operational levels, including Spa Receptionists, Spa Therapists, and Spa Attendants. The data were obtained through interviews, observation, texts collection, and informal consultation at several 'international' Spa outlets in Nusa Dua tourist resorts. They were then analyzed and are presented by using Hutchinson and Waters' (1987) and Mun by 's (1978) target situation analysis frameworks. The communicative acts and.functions can be grouped into 9 communicative events: information clerk, reservation clerk, reception clerk, bell boy/doorman, spa attendant, spa therapist, cashier, communicating by telephone, and dealing with complaints.